Research on entrepreneurship indicators - Giriūnienė, Gintarė (Buhalterinės apskaitos teorija ir praktika, 2014)
It should be noted that the optimal national economic promotion policy-making becomes more and more challenging, since economic growth is also more or less influenced by many external factors directly uncontrollable by the state. It is worthy of note that entrepreneurship is identified in economic literature as a very important factor directly influencing domestic economic activity and development despite the fact that there exists a large variety of entrepreneurship development needs and opportunities in different countries. An analysis of scientific literature has shown that the domestic entrepreneurial opportunity has indeed a significant impact on economic activity; however, the need for entrepreneurship has no effect on the national economy. Thus, for credible research, it is particularly important to analyze the very entrepreneurship-determining factors. While many of scientific literature sources argue that a key impact on entrepreneurship of a country is made namely by society, which chooses what to buy, how much money it has, and how it responds to one or another business, it should be emphasized that entrepreneurship is driven not only by consumers’ demands, but also by other entrepreneurship-determining factors, which can be divided into two main groups – internal and external. Comprehensive analysis of the factors influencing entrepreneurship demonstrates that self-employed individuals and companies have quite different opportunities for business development, leading to disparity in significance of internal and external factors that determine their entrepreneurship and effect on them. It should be emphasised that economic resources are quite restricted for self-employed persons and small businesses with relatively low capital in comparison with large enterprises; therefore, an impact of entrepreneurship-determining factors is extremely important to them. Findings of the research enable to suggest that a state, seeking to create a business and entrepreneurship development-friendly environment, must take into account not only the formation of internal and external factors determining the entrepreneurship, but also to evaluate an impact of the latter through two dimensions – self-employed individuals and companies in connection to the fact that all entrepreneurship-determining factors have a different significance and impact on these evaluation dimensions.